2013
DOI: 10.1111/mms.12053
|View full text |Cite
|
Sign up to set email alerts
|

Bottom side‐roll feeding by humpback whales (Megaptera novaeangliae) in the southern Gulf of Maine, U.S.A

Abstract: Humpback whales (Megaptera novaeangliae) are known for the variety and complexity of their feeding behaviors. Here we report on the use of synchronous motion and acoustic recording tags (DTAGs) to provide the first detailed kinematic descriptions of humpback whales using bottom side‐rolls (BSRs) to feed along the seafloor. We recorded 3,505 events from 19 animals (individual range 8–722). By animal, mean BSR duration ranged from 14.1 s to 36.2 s.; mean body roll angle from 80º to 121º, and mean pitch from 7º t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…One well-described foraging method used by humpbacks in the Gulf of Maine is bottom side-roll feeding on sand lance (Ammodytes spp.) near the sea floor, particularly during night-time hours [21]. Humpbacks have demonstrated flexible acoustic behaviour in the presence of noise [3,22,23], but few studies have investigated noise effects on their subsurface foraging behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…One well-described foraging method used by humpbacks in the Gulf of Maine is bottom side-roll feeding on sand lance (Ammodytes spp.) near the sea floor, particularly during night-time hours [21]. Humpbacks have demonstrated flexible acoustic behaviour in the presence of noise [3,22,23], but few studies have investigated noise effects on their subsurface foraging behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Within the SBNMS, the local abundance of humpback whales fluctuates with local sand lance abundance [ Payne et al ., ; Weinrich et al ., ] and humpback feeding behavior varies relative to sand lance behavior. For example, humpbacks feed along the bottom at night when sand lance bury in the substrate [ Friedlaender et al ., ; Hazen et al ., ; Ware et al ., ] and use bubble nets to forage in the upper portions of the water column during the day when sand lance leave the substrate to feed [ Friedlaender et al ., ; Wiley et al ., ]. In addition, the geographic distribution of feeding humpback whales within the SBNMS varies on a temporal basis ranging from hours to months, and these feeding locations are also thought to be highly influenced by sand lance aggregations.…”
Section: Introductionmentioning
confidence: 99%
“…; Ware et al . ). Tag studies have revealed that subsurface lunge feeding behaviour in fin whales ( Balaenoptera physalus ) and humpback whales ( Megaptera novaeangliae ) involves significant rolling moments, although the extent of the roll is typically 90‐degrees (Wiley et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Ware et al . ). Lunge feeding at the sea surface, which to date has only been analysed from ship observations, often involves a greater range of manoeuvring strategies (Kot et al .…”
Section: Introductionmentioning
confidence: 97%